2011
DOI: 10.1042/bst0391502
|View full text |Cite
|
Sign up to set email alerts
|

Proteases and caspase-like activity in the yeast Saccharomyces cerevisiae

Abstract: A variety of proteases have been implicated in yeast PCD (programmed cell death) including the metacaspase Mca1 and the separase Esp1, the HtrA-like serine protease Nma111, the cathepsin-like serine carboxypeptideases and a range of vacuolar proteases. Proteasomal activity is also shown to have an important role in determining cell fate, with both pro- and anti-apoptotic roles. Caspase 3-, 6- and 8-like activities are detected upon stimulation of yeast PCD, but not all of this activity is associated with Mca1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…With this respect yeast metacaspase-encoding gene YCA1 has been shown to be a positive regulator of yeast PCD induced by different stimuli [62], including acetic acid [13]. Yet, no apoptosome has been shown in yeast and a variety of proteases have been shown to participate in yeast PCD, not all of these activities being associated with YCA1 [6]. Importantly, we have previously shown and here confirmed that AA-PCD occurs both in WT and yca1 cells but with a lower death rate in the latter cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With this respect yeast metacaspase-encoding gene YCA1 has been shown to be a positive regulator of yeast PCD induced by different stimuli [62], including acetic acid [13]. Yet, no apoptosome has been shown in yeast and a variety of proteases have been shown to participate in yeast PCD, not all of these activities being associated with YCA1 [6]. Importantly, we have previously shown and here confirmed that AA-PCD occurs both in WT and yca1 cells but with a lower death rate in the latter cells.…”
Section: Discussionmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 6 Samples were analyzed using a split-free nano-flow liquid chromatography system (EASY-nLC II, …”
Section: Lc-esi-cid-ms/ms (Proteomic Analysis)mentioning
confidence: 99%
“…51 It is involved in degrading various cytosolic proteins in about 40% of the numerous apoptotic PCD scenarios initiated in response to a variety of stimuli. [52][53][54] Yca1p can be activated by: (1) ROS and/or cytochrome c released from mitochondria into the cytosol; 49,53,55 and (2) Nma111p, a serine protease which in the nucleus degrades Bir1p, the only presently known inhibitor of Yca1p (Fig. 9A).…”
Section: The Commitment Of Yeast To Liponecrotic Pcd Elevates the Extmentioning
confidence: 99%
“…The genetic analyses possible in yeast will be able to address whether functional overlap exists between proteases, or whether additional proteases exist that have not been ascribed a role in PCD control. In support of the latter possibility, protease activities that do not correspond to known caspase-like enzymes have been identified that are able to cleave fluorescent substrates with specificities similar to mammalian caspases (Wilkinson and Ramsdale 2011).…”
Section: Executioners Of the Programmed Cell Death Pathwaymentioning
confidence: 89%